Memory distrust and imagination inflation: A registered report - Iwona Dudek; Romuald Polczyk (PLoS ONE, 2025)
Imagination inflation occurs when the subjective confidence of a person that an event has occurred increases after they imagine it occurring. In this project, our primary aim was to test whether memory distrust is related to the imagination inflation effect in people who are aware of the discrepancies between their own memories and what they have imagined. Our secondary purpose was to investigate whether the influence of memory distrust on imagination inflation is moderated by traits that are described as disengagement from reality and to test whether memory distrust mediates the relationship between self-esteem and imagination inflation. In a three-step procedure, participants (N = 279) assessed their confidence that a list of childhood events occurred to them; then they imagined three of these events and reassessed their confidence. Half of the participants were subjected to a memory distrust induction procedure. To sensitize participants to discrepancies between actual childhood memories and imagined ones, some of them received cues about the source and/or perspective of the imagined events. Memory distrust as an individual trait was found to be unrelated to the imagination inflation effect. Furthermore, the expected effect of memory distrust as a state on susceptibility to the imagination inflation effect in groups sensitized to discrepancies was not confirmed. Therefore, it seems that people who we consider to be distrustful of their memory are no more susceptible to this type of memory distortion than memory trusters.